Virologic failure and mortality in older ART initiators in a multisite Latin American and Caribbean Cohort - Carriquiry, Gabriela (J Int AIDS Soc, 2018)
INTRODUCTION: The “greying” of the HIV epidemic necessitates a better understanding of the healthcare needs of older HIV‐positive adults. As these individuals age, it is unclear whether comorbidities and their associated therapies or the ageing process itself alter the response to antiretroviral therapy (ART). In this study, HIV treatment outcomes and corresponding risk factors were compared between older ART initiators and those who were younger using data from the Caribbean, Central and South America Network for HIV Epidemiology (CCASAnet). METHODS: HIV‐positive adults (≥18 years) initiating ART at nine sites in Argentina, Brazil, Chile, Haiti, Honduras, Mexico and Peru were included. Patients were classified as older (≥50 years) or younger (<50 years) based on age at ART initiation. ART effectiveness was measured using three outcomes: death, virologic failure and ART treatment modification. Cox regression models for each outcome compared risk between older and younger patients, adjusting for other covariates. RESULTS: Among 26,311 patients initiating ART between 1996 and 2016, 3389 (13%) were ≥50 years. The majority of patients in both ≥50 and <50 age groups received a non‐nucleoside reverse transcriptase inhibitor‐based regimen (89% vs. 87%), did not have AIDS at baseline (63% vs. 62%), and were male (59% vs. 58%). Older patients had a higher risk of death (adjusted hazard ratio (aHR) 1.64; 95% confidence intervals (CI): 1.48 to 1.83) and a lower risk of virologic failure (aHR: 0.73; 95% CI: 0.63 to 0.84). There was no difference in risk of ART modification (aHR: 1.00; 95% CI: 0.94 to 1.06). Risk factors for death, virologic failure and treatment modification were similar for each group. CONCLUSIONS: Older age at ART initiation was associated with increased mortality and decreased risk of virologic failure in our cohort of more than 26,000 ART initiators in Latin America and the Caribbean. To the best of our knowledge this is the first study from the region to evaluate ART outcomes in this growing and important population. Given the complexity of issues related to ageing with HIV, a greater understanding is needed in order to properly respond to this shifting epidemic.